2022
DOI: 10.3390/pathogens11020221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Betacoronavirus OC43 and SARS-CoV-2 Elimination by Zefero Air Sanitizer Device in a Novel Laboratory Recirculation System

Abstract: Indoor air sanitizers contrast airborne diseases and particularly severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/Coronavirus disease 2019 (COVID-19). The commercial air sanitizer Zefero (Cf7 S.r.l., San Giovanni La Punta, Italy) works alternatively using a set of integrated disinfecting technologies (namely Photocatalysis/UV mode) or by generating ozone (Ozone mode). Here we evaluated the virucidal efficacy of Zefero setup modes against human Betacoronavirus OC43 and SARS-CoV-2. For this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Buonanno et al 29 investigated the inactivation of aerosolized common cold coronaviruses and influenza, determining low doses ranging from 1.2 to 3.8 mJ/cm 2 to achieve 3‐log reduction, using far‐UV‐C light at 222 nm. Finally, only one study worked with SARS‐CoV‐2 using a commercial system employing UV‐C or ozone to inactivate this virus and the seasonal HCoV‐OC43 31 . Their experimental setup did not facilitate the determination of irradiation doses or recovery of infectious viruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Buonanno et al 29 investigated the inactivation of aerosolized common cold coronaviruses and influenza, determining low doses ranging from 1.2 to 3.8 mJ/cm 2 to achieve 3‐log reduction, using far‐UV‐C light at 222 nm. Finally, only one study worked with SARS‐CoV‐2 using a commercial system employing UV‐C or ozone to inactivate this virus and the seasonal HCoV‐OC43 31 . Their experimental setup did not facilitate the determination of irradiation doses or recovery of infectious viruses.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Although highly relevant, UV‐C mediated decontamination of aerosolized viruses, in particular SARS‐CoV‐2, is an understudied topic. We are aware of only four publications 28 , 29 , 30 , 31 trying to assess the stability of coronaviruses in aerosols. Walker et al, 28 demonstrated that murine beta coronaviruses aerosols are highly susceptible to 254 nm UV‐C‐irradiation, between 7 and 10 times more than adenoviruses and bacteriophage MS2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Hu et al [189] (2021) Aqueous 4.5, 9, 18, 36 mg/L 1, 5, 10 min Virus solution inoculated into Vero E6 cells) Full inactivation of virus stock (4 × 10 3 PFU/mL) in<1 min, by 36 mg/L aqueous ozonation. Nicolò et al [190] (2022) Gaseous 5 g/h in a chamber of 0.033 m 3 15, 30 min Aerosol sampling The virus was fully eliminated after 30 mins of ozone exposure. Takeda et al [191] (2021) Glycerol 200, 500, 1000, 2000 ppm 20 sec , 1 h, & 24 h Virus solution in DMEM and FBS media ≥99.91 % of the virus was inactivated by ozonated glycerol (500 ppm, 1 h) at 20 % of FBS concentration.…”
Section: Ozone In the Era Of Covid-19mentioning
confidence: 99%